Antioxidant activity of essential oil of oregano species from Argentina in relation to their chemical composition - Quiroga, Patricia Raquel (2011)
The purpose of this work was to determine chemical composition and antioxidant activity of essential oil of different oregano species from Argentina: 'Cordobes', 'Criollo', 'Mendocino' and 'Compacto'. The essential oil composition was determined by gas-liquid chromatography and mass spectrometry. Scavenging activity was analysed by DPPH test. The antioxidant activity of the essential oils was determined by an accelerated oxidation test in canola oil. Thirty-nine compounds were identified in the oregano essential oils. The oregano species showed differences in their chemical composition, radical scavenging activity and antioxidant activity. The main compounds in the studied oregano species were thymol and trans-sabinene hydrate followed by γ-terpinene, terpinen-4-ol and α-terpinene. The oregano, 'Criollo', was rich in γ-terpinene and had lower thymol and trans-sabinene hydrate and higher α-terpinene and carvacrol contents than the other oregano species. 'Mendocino' had higher trans-sabinene hydrate and limonene than the other oregano species. 'Cordobes' and 'Compacto' had higher thymol content, radical scavenging activity and antioxidant activity in canola oil.